The Correlation between English Department Students' Habit in Watching English Movies and Their Vocabulary Knowledge - Uena Apulisa; Novitri; Masyhur (JEE (Journal of English Education), 2021)
This research discussed the correlation between English department students' habit in watching English movies and their vocabulary knowledge. The background of conducting this research is to see how the possibility of students' habits in watching English movies influenced students' vocabulary knowledge. Furthermore, to find out if there is a significant correlation between English department students' habit in watching English movies and their vocabulary knowledge, this research determines the descriptive correlational method as the research design. After collecting and analyzing the data, it is obtained that the students' habit in watching English movies is categorized in the "high" habit category, and vocabulary knowledge is categorized in "good" ability, and significant correlation value is in moderate level correlation. In other words, it is implied that the students' habit in watching English movies was influenced to the acquisition of students' vocabulary knowledge.